Disseminated tuberculosis diagnosed first as leptospirosis in immunocompetent patient (Faculty of Medicine Universitas Indonesia, 2015)
Disseminated tuberculosis, mostly seen in immunocompromised patient, can affect several organs. The diagnosis can be difficult due to various clinical manifestations. A case of disseminated tuberculosis of lung and liver that develops acutely is rare especially in immunocompetent patient. Here, we present a 42 year old immunocompetent woman with lung and hepatic tuberculosis which was confirmed by characteristics histopathological findings of the liver biopsy.